Arthroscopic-Assisted Core Decompression for Osteonecrosis of the Femoral Head - Gupta, Anil K. (Elsevier, 2013)
The management of pre-collapse osteonecrosis of the femoral head is controversial. Core decompression is a technique that theoretically decreases the intraosseous pressure of the femoral head, resulting in a local vascularized healing response. Its efficacy has been shown in delaying early subchondral collapse. We describe the technique of arthroscopic-assisted core decompression of the femoral head for osteonecrosis. The advantages of this technique include evaluation of the presence or absence of articular cartilage injury, subchondral collapse, and guidance during reaming and curettage. It also allows the ability to address any concomitant soft-tissue or bony pathology associated with or in addition to the osteonecrotic lesion.